Ferroptosis-related gene expression in the pathogenesis of preeclampsia - Ding, Yuzhen; Yang, Xiaofeng; Han, Xiaoxue; Shi, Meiting; Sun, Lu; Liu, Mengyuan; Zhang, Ping; Huang, Zhengrui; Yang, Xiuli; Li, Ruiman (Frontiers in Genetics, 2022)
Background: Preeclampsia is one of the leading causes of maternal and fetal morbidity and mortality worldwide and its pathogenesis remains to be investigated. Ferroptosis is a form of regulated cell death, which is characterized by iron-dependent lipid peroxidation. However, the mechanism of ferroptosis in preeclampsia remains unclear. The aim of the study was to identify the key molecules involved in ferroptosis to further explore the mechanism of ferroptosis in preeclampsia. Methods: Gene expression data and clinical information were downloaded from GEO database. The limma R package was used to screen differentially expressed genes (DEGs) and intersected with ferroptosis genes. The GO and KEGG pathways were then analyzed. Next, hub genes were identified via weighted gene co-expression network analysis (WGCNA). Receiver operating curves (ROC) was performed for diagnostic as well as Pearson’s correlation of hub genes and clinicopathological characteristics. Immunohistochemistry and western blot analysis were used to verify the expression of hub genes. Results: A total of 3,142 DEGs were identified and 30 ferroptosis-related DEGs were obtained. Besides, ferroptosis-related pathways were enriched by GO and KEGG using DEGs. Two critical modules and six hub genes that were highly related to diagnosis of preeclampsia were identified through WGCNA. Analysis of the clinicopathological features showed that NQO1 and SRXN1 were closely correlated with preeclampsia characteristics and diagnosis. Finally, among these hub genes, NQO1 and SRXN1 were selected for validation. Conclusions: Our findings may provide relevant evidence for the role of ferroptosis in preeclampsia. Further studies are necessary to explore the deeper mechanisms of placental ferroptosis and its role in the preeclampsia pathogenesis.